UMUMKASBIY VA IXTISOSLIK FANLARNI KOGNITIV-VIZUAL YONDASHUV ASOSIDA O’QITISH ORQALI TALABALARNING KO’NIKMALARINI SHAKLLANTIRISH IMKONIYATLARI - Ya.Xo’jjiyev, M.; muhandislik, Buxoro (SCIENCE and SOCIETY, 2021)
Science achieves its goal by teaching special subjects in innovative ways. Possesses a high level of perception, understanding, interest and skills in delivering science to the student through the cognitive-visual training of engineering sciences. In this regard, the golden ideas of foreign scientists and innovative approaches to science, as well as information about what human factors should be taken into account in the perfect mastery of science.